Can the teaching of History change the social representations of boys and girls? A case study of students in Alicante - Olmos Vila, Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article presents the results of a research project carried out in Benidorm (Alicante, Spain) during the period 2015- 2016. It explores the social representations of young people between 16 and 18 years of age, in the face of the current political and economic situation: the causes, the solutions, and those responsible for the economic crisis. The adolescents that took part in this study are in secondary school, attend the same educational institution and come from similar socio-economic contexts. They were divided into two groups. One of the groups receives Contemporary History classes (Group A) and the other does not (Group B). The data was collected from a questionnaire with questions about the crisis, regarding images from the current socio-economic crisis and commentaries from historical sources about the crises of 1873, 1929 and 2008. The results show that the group that receives History classes is more critical when analyzing the current societal problems, as well as establishing analogies with the past to explain the situations of the present, whereas the other group reproduces the opinions of the media.